1986
DOI: 10.1128/jb.167.2.666-673.1986
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and transport of ferric enterobactin in Escherichia coli

Abstract: The specificity of the outer membrane protein receptor for ferric enterobactin transport in Escherichia coli and the mechanism of enterobactin-mediated transport of ferric ions across the outer membrane have been studied. Transport kinetic and inhibition studies with ferric enterobactin and synthetic structural analogs have mapped the parts of the molecule important for receptor binding. The ferric complex of the synthetic structural analog of enterobactin, 1,3,5-N,N',N"-tris-(2,3-dihydroxybenzoyl)triaminometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 44 publications
6
61
1
Order By: Relevance
“…14,15 However, synthetic analogs of enterobactin, which are not susceptible to this specific hydrolysis, can be 5% as effective as enterobactin in delivering iron to the cell, and thus sufficient for growth promotion. 16,17 This result implies the existence of a secondary pathway for intracellular iron release. While ferric enterobactin at neutral pH cannot release iron by reduction, 18,19 protonation of ferric enterobactin makes reduction much easier.…”
Section: Introductionmentioning
confidence: 95%
“…14,15 However, synthetic analogs of enterobactin, which are not susceptible to this specific hydrolysis, can be 5% as effective as enterobactin in delivering iron to the cell, and thus sufficient for growth promotion. 16,17 This result implies the existence of a secondary pathway for intracellular iron release. While ferric enterobactin at neutral pH cannot release iron by reduction, 18,19 protonation of ferric enterobactin makes reduction much easier.…”
Section: Introductionmentioning
confidence: 95%
“…1 Upper Left). The early studies of receptor binding and transport of FeEnt using a wide range of synthetic analogs showed that the coordinated catechol amide groups are essential and cannot be significantly changed without disrupting recognition, whereas the triserine macrocycle is not recognized and can be replaced with very different molecular scaffolds (34,61).…”
Section: Methodsmentioning
confidence: 99%
“…Iron release is through the action of the cytoplasmic esterase (32,33). However, synthetic analogs of enterobactin, which are not susceptible to hydrolysis, are Ϸ5% as effective in delivering iron (34), implying a secondary pathway of iron release. Unfortunately, perhaps because of previous errors, there continues to be confusion on this subject.…”
Section: Feent Structurementioning
confidence: 99%
“…Such concentrations, which may vary with diet, are insufficient for bacterial growth (34,36,47), but microorganisms capture iron from these environments (19) by the elaboration of high-affinity iron chelators (siderophores) (48), or by direct acquisition of the iron from eukaryotic proteins (19,37)). Certain gram-negative bacterial outer membrane (OM) proteins transport ferric siderophores (9,20,27,32,46,64), whereas others strip iron from transferrin and lactoferrin or use the heme within hemoglobin. These processes display specificity.…”
mentioning
confidence: 99%